Seagrass Meadow Conditions in Coastal Waters of Siwak Bay Central Lombok - Destiana, Elvina; Candri, Dining Aidil; Ahyadi, Hilman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Seagrass is a flowering plant thriving in shallow sea waters and estuaries. Seagrass ecosystems are essential in supporting life in shallow seas as primary producers, biota habitats, sediment trappers, and nutrient trappers. Environmental factors affecting seagrass growth include temperature, salinity, pH, and substrate. The study was conducted in March-June 2023. This study aimed to determine the type and condition of seagrass beds in the waters of Siwak Bay. The method used in this study is the quadrant transect method at three research stations. There are seven types of seagrass identified, namely Thalassia hemprichii, Halophila ovalis, Cymodocea rotundata, Cymodocea serrulata, Halodule pinifolia, Halodule uninervis, and Syringodium isoetifolium. The percentage of total seagrass cover is at a value of 37%-61%, indicating that the condition of seagrass beds in the waters of Siwak Bay is included in the unhealthy category. The highest species density found at station III in Halodule pinifolia was 483.5 stands/m², and the lowest was found at stations II and III in Thalassia hemprichii and Cymodocea serrulata with 0 stands/m². The average density value of seagrass beds in the waters of Siwak Bay is very dense. The highest type frequency was found in Cymodocea rotundata, with a value of 2.53. The tallest species diversity and diversity index was found at station II with values of 1.56 and 0.8, respectively. In contrast, the highest dominance index was found at station I, with a value of 0.44.